Hemostatic and hepatoprotective bioactivity of Junci Medulla Carbonisata-derived Carbon Dots - Cheng, Jinjun; Zhang, Meiling; Sun, Ziwei; Lu, Fang; Xiong, Wei; Luo, Juan; Kong, Hui; Wang, Qingguo; Qu, Huihua; Zhao, Yan (Nanomedicine (London, England), 2019)
To explore the hemostatic and hepatoprotective bioactivity of Junci Medulla Carbonisata-derived Carbon Dots (JMC-CDs). The JMC-CDs were characterized using transmission electron microscopy, HPLC, Fourier transform IR, UV, fluorescence and x-ray photoelectron spectroscopy. The hemostatic effect of JMC-CDs was evaluated and confirmed by trauma hemorrhagic animal models and internal hemorrhage animal model induced by venom. The JMC-CDs ranged in diameter from 1.0 to 8 nm and had a yield of 0.12%. Moreover, JMC-CDs not only possessed remarkable hemostatic efficacy but could also prevent hemorrhage-induced liver injury, as demonstrated by the reduced serum levels of biochemical indicators of liver damage such as aspartate aminotransferase, alanine amino transferase, alkaline phosphatase, total bilirubin and direct bilirubin. The JMC-CDs may have great potentials in clinical practice.